Whole genome sequences of a free-living Pseudomonas sp. strain ML96 isolated from a freshwater Maar Lake - Li, Xiuling; Blom, Jochen; Zeng, Yonghui (Marine genomics, 2015)
A free living freshwater Pseudomonas strain ML96 was isolated from the Huguangyan Maar Lake in southern China. Genome sequencing of strain ML96 revealed a 4.7 Mb long draft genome consisting of 47 contigs with a G+C content of 64.8%. Its 16S and 23S rRNA gene sequences were 99.8% and 99.3% identical to those of its closest relative, Pseudomonas alcaligenes NBRC 14159, respectively. ML96's genome shared 73% orthologous CDS (3256/4457) with the genome of NBRC 14159. Comparative genomics analysis provide further insight into the diversity and evolution of aquatic Pseudomonas species, which may help enhance our understanding of this both environmentally and medically important group of bacteria.
Keywords: Phylogeny; China; Water Microbiology; Lakes; Molecular Sequence Data; molekulární sekvence - údaje; mikrobiologie vody; fylogeneze; Pseudomonas; Genome, Bacterial; jezera; Čína; genom bakteriální